Improvement of Intangible Assets Accounting and Auditing (Texas Journal of Multidisciplinary Studies, 2022)
The following article reviews current problems of improving accounting and inventory of intangible assets in the organization. It reveals some measures to prevent financial loses and save incomes of organization properties.